Tumor and bone marrow uptakes on [18F]fluorodeoxyglucose positron emission tomography/computed tomography predict prognosis in patients with diffuse large B-cell lymphoma receiving rituximab-containing chemotherapy. Issue 45 (November 2017) - Chang, Chin-Chuan; Cho, Shih-Feng; Tu, Hung-Pin; Lin, Chia-Yang; Chuang, Ya-Wen; Chang, Shu-Min; Hsu, Wen-Ling; Huang, Ying-Fong
Abstract : Abstract: The purpose of this study was to determine the relevance of standardized uptake value (SUV) on [ 18 F]fluorodeoxyglucose (FDG) positron emission tomography/computed tomography (PET/CT), focusing on tumor and bone marrow, to disease outcomes based on progression-free survival (PFS) and overall survival (OS) in patients with diffuse large B-cell lymphoma (DLBCL) receiving rituximab-containing chemotherapy. We reviewed the records of patients with DLBCL who were diagnosed between September 2009 and January 2013 and underwent pretreatment whole-body FDG PET/CT scans. All patients received rituximab-containing chemotherapy. The maximal SUV of tumor (SUVt) and maximal SUV of sternum (SUVst) were measured. Univariate and multivariate analyses were used to assess the prognostic significance of SUVt, SUVst, gender, age, clinical stage, international prognostic index (IPI), and laboratory tests. There were total 70 patients enrolled in this study. The median follow-up time was 36 months. An SUVt cut-off value of ≥19 had the best discriminative yield for PFS ( P = .04). An SUVst cut-off value of ≥1.6 had the best discriminative yield for OS. The 3-year OS rates for patients with maximal SUVst < 1.6 and for those with maximal SUVst ≥1.6 were 74.8% and 57.1%, respectively ( P = .04). Further forward, multivariate Cox proportional hazards model revealed that maximal SUVst (hazard ratio: 2.62; 95% confidence interval: 1.10–6.28; P = .03) and IPI were significant factors affecting OS. In patients with DLBCL receiving rituximab-containing chemotherapy, elevated maximal SUVt ≥19 was an independent predictor for shorter PFS, and maximal SUVst ≥1.6 was an independent predictor for shorter OS. It adds the value of pretreatment FDG PET/CT scans. Abstract : Supplemental Digital Content is available in the text